2022
DOI: 10.1093/femsle/fnac083
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting of dikaryotic Pleurotus ostreatus nuclei using the CRISPR/Cas9 system

Abstract: Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9)-assisted gene targeting is a promising method used in molecular breeding. We recently reported the successful introduction of this method in the monokaryotic Pleurotus ostreatus (oyster mushroom), PC9. However, considering their application in mushroom breeding, dikaryotic strains (with targeted gene mutations in both nuclei) need to be generated. This is laborious and time-consuming because a classical crossin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Next, we examined whether a mutation was introduced into each of the four genes (vp2, vp3, mnp3, or mnp6) in each transformant using genomic PCR experiments. Our previous studies showed that the introduced plasmid(s) were often integrated at the target site of sgRNA in some of the P. ostreatus mutants obtained from the pCcPef3-126-based CRISPR/Cas9 (Boontawon, Nakazawa, Horii, et al, 2021;Boontawon, Nakazawa, Inoue, et al, 2021;Koshi et al, 2022;Yamasaki et al, 2022). This usually caused insufficient amplification from the mutants with large insertions due to the requirement of a longer extension time than the fragment amplified from the parental control strain.…”
Section: Isolation and Characterization Of Vp2/vp3/ Mnp3/mnp6 Quadrup...mentioning
confidence: 99%
“…Next, we examined whether a mutation was introduced into each of the four genes (vp2, vp3, mnp3, or mnp6) in each transformant using genomic PCR experiments. Our previous studies showed that the introduced plasmid(s) were often integrated at the target site of sgRNA in some of the P. ostreatus mutants obtained from the pCcPef3-126-based CRISPR/Cas9 (Boontawon, Nakazawa, Horii, et al, 2021;Boontawon, Nakazawa, Inoue, et al, 2021;Koshi et al, 2022;Yamasaki et al, 2022). This usually caused insufficient amplification from the mutants with large insertions due to the requirement of a longer extension time than the fragment amplified from the parental control strain.…”
Section: Isolation and Characterization Of Vp2/vp3/ Mnp3/mnp6 Quadrup...mentioning
confidence: 99%
“…However, these classical breeding methods are laborious and time-consuming. Thus, methodologies for more time- and cost-effective molecular breeding are needed (Yamasaki et al, 2022 ). The implementation of the CRISPR/Cas9 system in P. ostreatus will undoubtedly facilitate its molecular breeding.…”
Section: Application Progress Of Crispr/cas9 In Edible Fungimentioning
confidence: 99%
“…In addition to the monokaryotic P. ostreatus strain PC9, CRISPR/Cas9 has also been successfully performed on the dikaryotic P. ostreatus . In 2022, Yamasaki et al ( 2022 ) reported a plasmid-based CRISPR/Cas9 technique for transforming both nuclei of dikaryotic P. ostreatus , PC9 × #64, to generate strains with low basidiospore production ability. Meiosis-related genes mer3 or msh4 were selected as target genes to design two different sgRNAs.…”
Section: Application Progress Of Crispr/cas9 In Edible Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular breeding by modifying genomic sequences to alter the function and expression of genes of interest [ 1 ] or by introducing foreign DNA to the host chromosomal sequence [ 2 , 3 , 4 ] has been attempted with some mushrooms; however, this approach is not applicable to edible mushrooms because the mushrooms generated in this way are essentially genetically modified organisms (GMOs). Nonetheless, a new technology in molecular breeding has emerged recently, namely CRISPR-Cas9 gene-editing technology, which enables targeted modification of the genes or DNA sequences of certain functions [ 5 , 6 , 7 , 8 ]. It has been applied to generate a new strain of A. bisporus that is resistant to browning via gene-editing of polyphenol oxidase (PPO) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%